The 30-day sobriety solution : how to cut back or quit drinking in the privacy of your own home - Canfield, Jack, 1944-; Andrews, Dave, 1972- (New York : Atria Books, 2016)
"Jack Canfield, the #1 New York Times bestselling author of the Chicken Soup for the Soul; franchise and coauthor of The Success Principles, and Dave Andrews, a recovery expert, join forces to present a revolutionary program to help you cut back or quit drinking entirely--in the privacy of your own home. Alcohol kills one person every ten seconds worldwide, according to the World Health Organization. Thankfully, now, for anyone who feels that alcohol has become a problem--and for the 23.5 million Americans living in recovery and looking to be reinspired--this new program introduces a groundbreaking model for sobriety that you can achieve in your own home. The 30-Day Sobriety Solution grew out of Jack Canfield's decades-long work in self-esteem and success training. Its principles were carefully developed into a program by Dave Andrews and tested by thousands whose amazing stories of recovery are shared throughout the book. Organized into five phases that span 30-day periods, this book guides you through each day with practical exercises that, over time, allow you to more easily make positive choices again and again. "The Sobriety System" is an empowerment program that moves systematically from beliefs (including limiting ones) to feelings and emotions to concrete actions and behaviors that promote better outcomes. Integrating neuroscience, cognitive therapy, proven tools, and teachings, The 30-Day Sobriety Solution is a clear, practical daily program that will help you achieve your goals--whether that's getting sober or just cutting back--and create positive, permanent change in your life"--
"A groundbreaking program to help you cut back or quit drinking entirely--in the privacy of your own home"--
Includes bibliographical references and index.
Keywords: Alcoholics -- Rehabilitation; Controlled drinking; Alcoholism -- Treatment